Analisis Sambungan Antara Balok Iwf dengan Kolom Baja Akibat Beban Siklik - Eko Riyanto (Universitas Muhammadiyah Yogyakarta, 2019)
AbstrakPenggunaan tabung baja dengan isian beton dapat meningkatkan kekuatan gaya aksial pada kolom. Selain itu, tabung baja berfungsi juga sebagai bekisting untuk inti beton. Penelitian ini bertujuan untuk mengetahui perilaku histeristis, kekuatan, kekakuan serta pola keruntuhan pada sambungan dalam menahan beban siklik. Dalam penelitian ini, dibuat dua buah benda uji yaitu benda uji sambungan menerus balok-kolom tabung baja dengan isian beton dan benda uji sambungan menerus balok-kolom tabung baja tanpa adanya isian beton. Sambungan sayap pada profil IWF yang menghubungkan kolom dan balok dibuat menembus kolom tabung baja dan dilas pada permukaan kolom. Benda uji dibebani dengan siklus beban yang mengacu pada ACI 374.1-05. Hasil pengujian menunjukkan benda uji dengan sambungan balok-kolom tabung baja isian beton memiliki histeresis lebih besar dari kolom tabung baja tanpa isian beton. Benda uji memiliki kegagalan tipe daktilitas parsial jika sebagai kriteria untuk memenuhi strong column weak beam. AbstractThe use of steel tube columns has several advantages including: steel tubes also function as formwork for concrete cores, with the presence of concrete fillers in steel tubes, the compressive strength of steel tubes against axial forces will also increase. In addition the steel tube serves to prevent cracks in the concrete, and the composite column greatly increases stiffness and significant strength compared to the construction of steel frames and ordinary reinforced concrete. The connection between beams and steel tube columns must have sufficient strength to withstand earthquake loads. This study aims to determine the ability of beam joints with columns and to know the strength, as well as the pattern of joint collapse in resisting cyclic loads. In this study, a continuous steel beam column column test specimen was made with concrete fillings and continuous test specimens of steel tube columns without concrete filling. The wing joint on the IWF profile that connects columns and beams is made through steel tube columns and welded to the column surface. The test object is loaded with the load cycle referred to in ACI 374.1-05. The test results showed that the steel tube column-beam joint test object with concrete filling had a hysteresis loops larger than steel tube columns without concrete filling. The test object has a partial ductileity type failure as a criterion of strong colun weak beam.